Prevalence and pattern of congenital heart diseases in Karimnagar, Andhra Pradesh, India: diagnosed clinically and by trans-thoracic-two-dimensional echocardiography - Jatav, Rajendra Kumar; Kumbhare, Mamta B.; Srinivas, Madoori; Rao, Davu Renuka; Kumar, P. Goutham; Reddy, P. Rohan; Manjusha, M. (International Journal of Research in Medical Sciences, 2017)
Background: To find the prevalence and pattern of congenital heart diseases (CHD) at a Semi-Urban teaching hospital in Karimnagar, Andhra Pradesh, India. Methods: A thorough history, clinical examination and Trans-Thoracic-Two-Dimensional Echocardiography (TTE) was done for all the live birth, children up to 18years of age and patients between 18 to 25 years, who were referred or presented to the Department of Medicine, Chalmeda Anand Rao Institute of Medical Sciences, Bommakal, Karimnagar (AP), over a period of 5 years from July 2008 through June 2013. Those suspected to having a CHD or referred in our department, were further evaluated with: Clinically, Twelve-Lead-Surface Electrocardiography, Chest Radiography and the diagnosis was confirmed by TTE. Trans-Thoracic-Two-Dimensional Echocardiography, M-Mode, Color flow doppler and Spectral doppler echocardiography was done in all patients in the various views. Results: Total 13,554 patients were examined and underwent TTE. Out of 13,554 patients 116 were identified as having congenital heart diseases, thus giving a prevalence of 8.55 per 1,000 live births. Isolated Ventricular septal defect (28.44%), isolated atrial septal defect (18.10%), Patent ductus arteriosus (10.34%), isolated congenital pulmonary stenosis (6.03%) and tetralogy of Fallot’s (6.03%), were the commonest defects observed and confirmed by TTE. TOF was the main cyanotic CHD (6.03%), with the prevalence of 0.51% per 1,000 live births. VSD, ASD and PDA were more prevalent in males. TOF and Complete A.V. Canal defect was prevalent in females. All small size muscular and perimembranous VSD was closed spontaneously. Spontaneous closure rate of 75.00% in Muscular VSD and 52.17% in perimembranous VSD was observed. Spontaneous closure rate of Ostium secundum type ASD was 53.33%. Conclusions: The prevalence of CHD at a tertiary teaching hospital (CAIMS, Bommakal, Karimnagar, AP, India), is 8.55 per 1,000 live births. VSD, ASD, PDA are the most common acyanotic and TOF was the commonest cyanotic congenital heart defects respectively. Non-Invasive Cardiac diagnostic technique (like TTE) plays major in the diagnosis of CHD. When clinical evidences lead to suspicion of congenital heart defect, an echocardiography should be performed immediately.